Riscos ambientais da ocupação urbana no entorno de águas superficiais: o caso do córrego Mingau, no bairro Parque Amazônia, em Goiânia - GO - Assunção, Simone Gonçalves Sales de (2002)
This dissertation evaluates the risks to surface waters in the municipality of Goiania posed by urbanization, based on a case study of 284,437.68 square meters in the Parque Amazonia neighbourhood. This includes all of the area drained by Mingau creek (a tertiary tributary of the Rio Meia Ponte), ranging from its main sources to the point where it drains into a larger stream. The Ecological Risk Analysis Method (FARIA, 1996) was used in this case study. This method gives the degree of risk through a combination of the sensitivity of a natural factor to damage through anthropic uses with the intensity of potential damages caused by anthropic use of this same factor. The analysis indicated a high level of risk in the areas of permanent preservation called for in the Forest Code and in State legislation, represented by strips of 100 meters around the sources and 50 meters along the creek, given that none of the area studied contains riverine forest in excellent condition. On the contrary, these areas are subject to the following activities that have compromised water quantity and quality and the physical integrity of the creek, whose sources have even been closed off and channeled for private use: leisure clubs, paint and tinsmith workshops, dump sites, drainage canals, agriculture and horticulture, human occupation and paved roads. The results of the analysis make reference to suggestions for ways in which to control or mitigate the ecological damage in the area of the creek and its environs and also to orient the overall urban planning of the capital of the state of Goiás so as to insure environmentally sustainable development.